Effect of particle size and resin content on leucaena leucocephala particleboard properties / Jamaludin Kasim ...[et al.] - Kasim, Jamaludin; Firdaus, Muhammad Adib; Ahmad, Nurrohana; Wan Abdul Rahman, Wan Mohd Nazri (2014)
This research was carried out to investigate the effect of particle size and resin content on mechanical and physical properties of particleboard made from Lellcaena lellcocephala species. The Lellcaena tree was harvested from UiTM Jengka forest. 24 boards were made from different particle sizes which are 1.0mm, 2.0mm, and 1.0mm + 2.0mm (mix). The resin content for three different types of particle size was 8%, 10%, and 12%. Urea formaldehyde (UF) was selected in this research. The press condition for the particleboard was 180°C at duration of 6 minutes. The mechanical properties in static bending for modulus of rupture (MOR), modulus of elasticity (MOE), tensile perpendicular, water absorption and thickness swelling were found to be significantly affected by the varying particle sizes and resin content used in the study. All boards passed the minimum requirements of BS EN Standards except for the dimensional propet1ies. Leucacealla leucocephala wood is a potential source of raw material for the wood composite industry.